Предмет: Математика,
автор: AlexandraRen
Упростить выражение. а^8-а^4/а^2(а^4+а^2)
Ответы
Автор ответа:
0
Ответ:
Пошаговое объяснение:
Автор ответа:
0
Ответ:
а^2 - 1.
Пошаговое объяснение:
(а^8-а^4)/(а^2(а^4+а^2)) = (а^4•(а^4 - 1))/(а^4•(а^2 + 1)) = (а^4 - 1)/(а^2 + 1) = ((а^2 - 1)•(а^2 + 1))/(а^2 + 1) = а^2 - 1.
Похожие вопросы
Предмет: Химия,
автор: sofiakolesnik53
Предмет: Литература,
автор: mihailsolovev12
Предмет: Другие предметы,
автор: cocortp
Предмет: Алгебра,
автор: пацанизварфеса
Предмет: Литература,
автор: gryazeva1984